(untitled) (Anwer Khan Modern Medical College Journal, 2018)
Background: Fournier’s gangrene is a vascular disaster of infective origin occurring about male external genitalia. Diabetes Mellitus is an important predisposing factor. A good number of patients of this rare clinical entity are admitted frequently in our centre. Till now the disease has the potential for significant morbidity and also mortality. Objective: The study was designed to be conducted among patients suffering from Fournier’s gangrene to identify the possible source of sepsis, to denote pattern and extent of area involvement and microorganisms isolated and to observe the treatment course and outcome. Methods: This prospective observational study was carried out in BIRDEM General Hospital, Dhaka among 60 patients of Fournier’s gangrene admitted under surgery department during the period of October 2016 to January 2018 using purposive sampling method. Result: The results of this study suggest that majority of the study population were in 51 to 60 years (Mean 52±4.9) age group. All the patients were diabetic with grossly elevated blood glucose level (Mean RBS=17.3 mmol/dl). In addition to scrotum, perineum, penis, buttock and lower abdomen were also affected to variable extent (73.3%). All patients required major debridement which had to be repeated in 68.3% cases. Steptococcus pyogens was the most common organism isolated (43.3%) followed by Eschericia coli (35%) and majority were of polymicrobial type (61.6%). Mortality rate was 8.3%. Conclusion: The diagnosis and treatment of Fournier’s gangrene is enigmatic and challenging to the physician. Urgent surgical debridement along with other appropriate supportive measures can reduce morbidity and mortality. Anwer Khan Modern Medical College Journal Vol. 9, No. 2: Jul 2018, P 124-130